Comparative study of physico-chemical properties of soil according to the age of aquaculture pond of Bangladesh - Siddique , M.A.M.; Barua , P.; Ghani , M.H. (Mesopotamian Journal of Marine Sciences, 2022)
Soil quality is an important factor in fish pond productivity as it controls pond bottom stability, pH of overlying water and concentrations of plant nutrients required for the growth of phytoplankton. A satisfactory site for constructing fishponds is that where the soil is very deep with neutral pH, weather infiltration is very low; mineralization of organic matter takes place rapidly. The present study was carried out to assess different soil parameters in different aged ponds and to find out the relationship between different aged ponds with different bottom soil parameters. Three groups of ponds (1-5 years, 6-10 years and above 10 years) were analyzed. There was no significant change of soil pH among different aged ponds. Significant variations were observed in textural compositions of different aged group pond’s soil. Mean percentages of clay and silt were found to be increasing with the increase of pond’s age. Amount of organic matter and organic carbon also increased sharply with the increasing of pond’s age. No significant variation were found from different aged group ponds for soil pH but the amount of organic matter, organic carbon, silt and clay were significantly increased with the increasing of pond age that may deteriorate the quality of pond’s bottom soil.